Pseudocyphellae ontogeny and thallus anatomy in species of Punctelia Krog (Parmeliaceae, lichenized Ascomycota) - Zanetti, Camila Aparecida [UNESP]; Barbosa, Suzana Bissacot [UNESP]; Adachi, Sergio Akira [UNESP]; Marcelli, Marcelo Pinto (Soc Botanica Brasil, 2017)
The genus Punctelia has been traditionally characterized by the type and distribution of pseudocyphellae, medullary chemical substances and the shape of conidia, whereas its species have been distinguished using mainly the shape, location, abundance and size of pseudocyphellae. Given that Punctelia is not monophyletic, additional studies are needed to determine its current delimitation. The present study used conventional techniques for structural studies using optical and scanning electron microscopy in order to describe and compare the structure and ontogeny of the pseudocyphellae of five species of Punctelia. The main differences among the studied species involve the type of pseudocyphellae development, the presence or absence of an epicortex cover and the organization and structure of the upper cortex. In one group of species the pseudocyphellae are formed from the outside to the inside of the thallus; in the other group, pseudocyphellae formation begins with the organization of medullary hyphae into circular groups in specific places. The present study contributes to the understanding of the structure and ontogeny of pseudocyphellae.
Keywords: aeroplectenchyma; lichen anatomy; light microscopy; Parmeliaceae; plectenchyma; pseudocyphellae; Punctelia